SS-31: A promising therapeutic agent against bleomycin-induced pulmonary fibrosis in Mice - Quankuan Gu; Yunlong Wang; Haichao Zhang; Wei Yang; Xianglin Meng; Mingyan Zhao (PLoS ONE, 2025)
Objective The aim of this research was to investigate if the mitochondria- targeting peptide SS-31 could serve as a protective measure against bleomycin-induced pulmonary fibrosis in mice. Method Mice were split into four groups named CON group, SS-31 group, BLM group, and the BLM + SS-31 group. SS-31 (intraperitoneal injection, 5mg/Kg) was administered daily from the day prior to the experiment for the control and model groups. Mice were euthanized after 28 days of the experiment, following which blood, bronchoalveolar lavage fluid, and lung tissue were collected for analysis. Results BLM caused a large decrease in body weight in mice. However, the intraperitoneal injection of SS-31 slowed down the body weight loss in the mice. It was observed through HE and Masson staining, immunohistochemistry, hydroxyproline detection, and fibrosis index measurement via Western blot that SS-31 could alleviate pulmonary fibrosis caused by BLM. Electron microscopy and ATP detection further suggested that SS-31 might help protect mitochondrial structure and function. It was also found that SS-31 could reduce reactive oxygen species and myeloperoxidase, thereby alleviating the reduction of antioxidant factor MPO and SOD, as well as diminishing the inflammatory factors TNF-α, IL-1 β, and IL-6. Conclusion The mitochondria-targeting drug SS-31 exhibited potential in mitigating bleomycin-induced pulmonary fibrosis, improving mitochondrial structural and functional damage, stabilizing the balance between oxidative and antioxidant systems, reducing inflammatory factor expression, and improving apoptosis in lung tissue.